Podcast Making Training as Creative Teaching Media For SDI Al Hakim Boyolangu Tulungagung Teachers - Rohmah Ivantri (PT FORMOSA CENDEKIA GLOBAL, 2023)
The world of education that is increasingly developing requires teachers to improve their abilities in teaching. One of the abilities that must be improved is the ability to produce creative teaching media. This training was held to help teachers at SDI Al-Hakim to improve their skills in producing digital-based creative teaching media in the form of podcasts. The teacher's ability to teach is an asset for teachers to make learning more creative and innovative. The selection of using the Asset Based Community Development (ABCD) method for community service at SDI Al-Hakim is dedicated to teachers at SDI Al-Hakim to be able to form digital-based creative media (podcasts) properly and smoothly.